Genome editing in plants by engineered CRISPR-Cas9 recognizing NG PAM - Endo, M.; Mikami, M.; Endo, A.; Kaya, H.; Itoh, T.; Nishimasu, H.; Toki, S.
Streptococcus pyogenes Cas9 (SpCas9)is widely used for genome editing and requires NGG as a protospacer adjacent motif (PAM). Here, we show that the engineered SpCas9 (SpCas9-NGv1)can efficiently mutagenize endogenous target sites with NG PAMs in the rice and Arabidopsis genomes. Furthermore, we demonstrate that the SpCas9-NGv1 nickase fused to cytidine deaminase mediates C-to-T substitutions near the 5' end of the target sequence.
Keywords: CRISPR